Pathological Findings in Wild Rats (Rattus rattus) Captured at Guafo Island, Northern Chilean Patagonia. Issue 2 (August 2017) - Seguel, M.; Muñoz, F.; Paredes, E.; Navarrete, M.J.; Gottdenker, N.L.
Summary: The black rat ( Rattus rattus ) is an invasive species and potential reservoir of significant pathogens of man, domestic animals and wildlife. During the 2012–2014 austral summers, 201 black rats were captured and examined on the uninhabited Guafo Island, in Northern Chilean Patagonia (43.593029°S, 74.713481°W). The mite Ornithonyssus bacoti caused lymphoplasmacytic and eosinophilic dermatitis in all infected rats (105/210, 52%), but no skin lesions were observed in rats infected with Nosopsyllus spp. and Plocopsylla spp. fleas. Eighty-eight rats (44%) had mild lymphoplasmacytic and eosinophilic enterocolitis and 61 of these rats were infected with the nematode Heterakis spumosa . In the liver, 63 animals (31%) had areas of necrosis with histiocytic and eosinophilic inflammation associated with multiple Calodium hepaticum eggs, and in 15 cases there was co-infection with several Taenia taeniaeformis strobilocerci. Mild interstitial lymphoplasmacytic sialadenitis with intranuclear inclusion bodies, suggesting cytomegalovirus infection, was observed in 28 rats (15%). In the lung, alveolar histiocytosis (69 rats, 34%) and perivascular lymphocytic infiltrates (46 rats, 23%) were the most common findings. There was mild to moderate lymphoplasmacytic interstitial nephritis in 52 rats (26%) and in 15% of these cases Leptospira spp. antigen was detected in the distal renal tubules. Some of the diseases of black rats on Guafo Island are likely to play a role in rat population dynamics. The endemic Guafo Island long-clawed mole mouse ( Geoxus lafkenche ), sea lions and fur seals may be at risk for infection by some of these rat pathogens. Graphical abstract: